Dialogowość w dawnej noweli włoskiej - Salwa, Piotr (Przestrzenie Teorii, 2008)
In the article are discussed various aspects of dialogic character, which appear in Boccaccio's Decameron and which are signalled or discussed by the author himself (a dialogue inside the text, intertextual dialogue, thematised dialogue, a dialogue with the reader and the like). Against this background the narrative strategies used by the so called "imitators" of the Tuscan writer, who discard his innovative view are interesting. Some of them ostentatiously "do not notice" this problem at all, others deprive dialogue of its open and ambiguous character, still others make it fit the needs of political persuasion. This attitude is more precisely illustrated by means of an example of Novelle - Short Stories of Giovanni Sercambi of Lucca and the original novel II Paradiso degli Alberti attributed to Giovanni Gherardi da Prato (these two Tuscan works of literature come from the 1 5th century).